Enhancing operational efficiency: a comparative case study of wuantanite and competitors in Bangladesh and financial overview of quantanite - Arafath, MD. Rabbi (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.